LINC00467 enhanced the proliferative, migratory and invasive ability of breast cancer cells by targeting miR-18a/b-5p/MAPK4 axis: LINC00467 enhanced cell growth of breast cancer - Zhang, Zhitao; Lan, Huan; Zhao, Shuai (Cellular and Molecular Biology, 2023)
Breast cancer (BC) is a common gynaecological malignancy worldwide. Long noncoding RNAs (lncRNAs) were identified to take part in the regulation of the occurrence and development of tumors. LncRNA The role of LINC00467 in lung adenocarcinoma has been reported, but its mechanism remains unclear in BC. To explore the role of LINC00467 deeply, we designed and performed a series of experiments. According to the result, it was discovered that LINC00467 was overexpressed in BC tissues and cells, and then the knockdown of LINC00467 resulted in a decline in cell growth and metastasis. Mechanistically, miR-18a/b-5p was screened out and validated to bind with LINC00467. Additionally, LINC00467 was negatively correlated with miR-18a/b-5p. Hereafter, there is evidence that miR-18a/b-5p targets MAPK4. Rescue assays suggested that MAPK4 amplification recovered the inhibitive effect of LINC00467 knockdown on cell growth and metastasis. In a word, LINC00467 enhanced BC cell growth and metastasis by targeting miR-18a/b-5p/MAPK4, which implies a potential revelation for exploring the therapeutic tactic of BC.